Expressing Islam religious life and politics in Indonesia - Fealy, Greg 1957-; White, Sally 1967- (Indonesia update series, 2008)
Examines some of the myriad ways in which Islam is being expressed in contemporary Indonesian life and politics. This book gives insights into such topics as the marketisation of Islam, contemporary pilgrimage, the rise of mass preachers, gender and Islamic politics, online fatwa, and trends among Islamist vigilante and criminal groups